THE ROLE OF THE MIGRATION FACTOR IN THE FORMATION OF RURAL COMMUNITIES OF MEDIEVAL DAGHESTAN (ON THE EXAMPLE OF THE SETTLEMENT OF EMELTA) - Hapizov, Sahban Magomedovic; Galbacev, Surhaj Magomedovic (History, Archeology and Ethnography of the Caucasus, 2018)
The paper is devoted to the study of the processes of integration of large rural communities in the Andi Koisu (Andi-Or) valley in the 15th-16th centuries. Also considerable attention is paid to migration from this valley to foothill Daghestan in the 16th century. Based on written sources, epigraphics and oral traditions, an attempt is made to reconstruct these historical processes. This analysis is based, mainly, on the example of the abandoned in the 16th century settlement Emelta, located in the south of the Gumbet district of Daghestan. The authors found a number of epigraphic monuments allowing more accurate dating of these processes. Epitaphs also allow to enrich understanding of the medieval anthroponomy of the Avars. A number of names have been identified, the existence of which has not been known until now. In Arabic epigraphy, Christian names were also revealed, in particular, Gusan. The authors also tried to give a general description of the toponymy of the investigated area. The use of a wide range of sources allowed to conduct the study, the results of which outline general features of migration processes and clarify not only the reasons, but also the consequences of them. As a result of the crisis and the gradual collapse of the medieval state of Sarir, mountainous Daghestan in the 14th-15th centuries was prone to internecine strife. This circumstance made economically successful small settlements inhabited by single related groups, unable to repel attacks of neighboring large communities or feudal bodies. As a result, a part of them disappeared without a trace together with residents who were the victims of epidemics or devastative attacks, but most were resettled in old or newly emerged large rural communities.
Keywords: Sinoykism; village; Avars; epigraphy; patronymy